The effects of muscle strengthening on neuro-musculo-skeletal dynamics in a squat jump: a simulation study - Prokopow, P. (Human Movement, 2011)
Purpose. The aim of this study was to quantitatively investigate the effects of muscle strengthening in a vertical squat jump based on a neuro-musculo-skeletal model and a forward dynamics simulation. Methods. During simulation trials, 16 major muscle groups of the lower extremities were gradually strengthened up to 20%. Results. Complex yet systematic deviations in body kinematics, kinetics and the neural control pattern were observed as a result of gradual muscle strengthening. Conclusions. Based on the generated results it was concluded that: (i) the pattern of kinematical changes depends on which muscles are strengthened, while the magnitude of the changes depends on how much the muscles are strengthened. (ii) Adjustment of muscle coordination, in some cases, can be performed without adjustment of neural control. (iii) The adjustment of neural control is done in an adaptive manner. (iv) Inter-segmental coordination is further altered if a smaller number of muscles are strengthened. (v) The main effect of equally strengthening all the muscles is an increase in joint torque, which is proportional to the increase in muscle strength.